Pilgrims Speaking Angry Words: Change and Anger in Chaucer’s Canterbury Tales - Huriye Reis (Ideas: Journal of English Literary Studies)
Medieval literature presents emotions such as anger as negative and destructive for the development of the medieval subject and society and defines anger not as a positive constructive affect but as an emotive reaction that should be suppressed, controlled or avoided. Chaucer’s Canterbury Tales, written against a background of tremendous change generated by political and religious conflict, the Black Death and the Peasants’ Revolt, acknowledges anger as an essential element of medieval culture although it does not give much space to the causes of it. The Canterbury pilgrims experience and perform anger as a result of the unstructured and fast change taking place in the traditional stabilities. Indeed, the changing society represented by the pilgrims in the Canterbury Tales appears to have anger issues and accordingly is characterised by situations of conflict and emotional crises. The pilgrims are presented as failing in terms of conformity and obedience to the regulatory principles of the feudal structure also because they foster anger and have angry responses when they are expected to suppress, avoid and control their anger. Anger in this context is presented as an essential element of the new culture that produces it. This paper reads Chaucer’s representation of anger as an affect/emotion in the Canterbury Tales and argues that as an emotive/affective agent, anger performed by the defiant pilgrims represents and forms the cultural response to the pervasive change and its results in the medieval feudal social structure represented in the Canterbury Tales.